Coincidence Point Results on Relation Theoretic Fw, Rg-Contractions and Applications. (11th June 2021) - Aslam, Muhammad; Aydi, Hassen; Batul, Samina; Naz, Amna
Abstract : Motivated by the ideas of F -weak contractions and F, R g -contractions, the notion of F w, R g -contractions is introduced and studied in the present paper. The idea is to establish some interesting results for the existence and uniqueness of a coincidence point for these contractions. Further, using an additional condition of weakly compatible mappings, a common fixed-point theorem and a fixed-point result are proved for F w, R g -contractions in metric spaces equipped with a transitive binary relation. The results are elaborated by illustrative examples. Some consequences of these results are also deduced in ordered metric spaces and metric spaces endowed with graph. Finally, as an application, the existence of the solution of certain Voltera type integral equations is investigated.